Generation of an ultra-stable dual-wavelength ytterbium-doped fiber laser using a photonic crystal fiber - Ahmad, Harith; Salim, M.A.M.; Azzuhri, Saaidal Razalli; Soltanian, M.R.K.; Harun, Sulaiman Wadi; Yasin, M. (IOP Publishing, 2015)
This paper describes the demonstration of a simple ytterbium-doped fiber (YDF) laser that utilized a short length of photonic crystal fiber (PCF) in a ring cavity and adjustments to the polarization state of an incorporated polarization controller (PC) to achieve a stable dual-wavelength output. The dual-wavelength lasing operation exploited the Mach-Zehnder interferometer effect, and the laser output consistently achieved high power stability with a 0.8 dB fluctuation over a period of 30 min. This proposed setup has the capability for adjustable spacing of two lasing wavelengths from a minimum of 0.40 nm to a maximum of 3.40 nm, allowing for flexibility in dual-wavelength laser generation in addition to stable and reliable system features.